Management and Business Analysis of Common Carp (Cyprinus carpio) at the Aquaculture Installation (IPB) Pandaan - Riyasya, Muhammad Indra; Rahim, Andi Rahmad (Jurnal Biologi Tropis, 2024)
The growing global population increases the demand for protein, making the aquaculture and fisheries industries vital. This study aims to optimize goldfish hatchery management at the IPB Pandaan, East Java, to improve production and seed quality. The research was conducted in January-February 2024 at the IPB Pandaan Fisheries Breeding Installation, using observation and interview methods. Primary data were obtained from interviews with business actors and stakeholders, while secondary data were from literature studies. Data analysis includes production management, water quality, feed, and financial evaluations such as R/C Ratio, BEP, and PP to assess performance and potential efficiency improvements in the goldfish hatchery business. Goldfish hatchery management at IPB Pandaan includes pond preparation, broodstock selection, spawning with temperature and water quality control, egg hatching, feeding, nursery, and seed harvesting. Water quality is maintained with temperatures of 23.9-30.5 ºC, pH 7.3-8.9, and DO 3.2-6.3 ppm. Total investment is Rp 37,500,000, with fixed monthly costs of Rp 3,335,414 and operational costs of Rp 500,000. The total revenue is Rp 7,784,000, and the profit is Rp 3,752,752. An R/C Ratio of 1.93 indicates a profitable business, with a payback period of 16.39 months and a BEP production price of Rp 14,497 per cup.